IMPLEMENTASI PENDIDIKAN NILAI DALAM PENDIDIKAN AGAMA ISLAM - ade Imelda (Universitas Islam Negeri Raden Intan Lampung, 2015)
Education is at the core values of Islamic religious education, for the purpose of education is to educate the value of human behavior in the teachings of Islam, better known by educating noble character is based on the Quran and Hadith. Through education values, the objectives, materials, methods, evaluation, and educators in Islamic religious education should support the achievement of educational goals that value. Implementation of values education since Islamic religious education can help learners become humans who understand the values of their religion and apply these values in their daily lives, so that any negative effects of the changing times can be anticipated with better learners.